Archaeal Communities: The Microbial Phylogenomic Frontier - Medina-Chávez, Nahui Olin; Travisano, Michael (Frontiers in Genetics, 2022)
Archaea are a unique system for investigating the diversity of life. There are the most diverse group of organisms with the longest evolutionary history of life on Earth. Phylogenomic investigations reveal the complex evolutionary history of Archaea, overturning longstanding views of the history of life. They exist in the harshest environments and benign conditions, providing a system to investigate the basis for living in extreme environments. They are frequently members of microbial communities, albeit generally rare. Archaea were central in the evolution of Eukaryotes and can be used as a proxy for studying life on other planets. Future advances will depend not only upon phylogenomic studies but also on a better understanding of isolation and cultivation techniques.